Conceptualising scientific theory-law relationship among preservice teachers with different academic abilities in science / Jasmine Jain and Johan @ Eddy Luaran - Jain, Jasmine; Luaran, Johan @ Eddy (Universiti Teknologi MARA, 2020)
For learners to achieve science literacy and become effective citizens who can make informed judgement on science-related issues in their daily lives, many studies have called for robust understanding of Nature of Science (NOS) among science learners. This study echoed the same sentiment, focusing on an aspect of NOS- the relationship between scientific theories and laws, among first year pre-service teachers. In this phenomenographic study, 10 participants were involved to address two research questions, which are (1) What are the varied ways first-year pre-service teachers experienced NoS, specifically pertaining to the relationship between scientific theories and laws? (2) What is the variation in conceptions held by firstyear pre-service teachers about the scientific theory-law relationship based on their academic ability in science? The findings suggest that the participants still conceptualise science knowledge as an objective epistemology, with 2 main categories of how theory-law relationship can be conceptualised. It was also found that there is no difference in terms of conceptualising these NOS aspects among participants of different academic science abilities. This paper also discusses the findings in relation to the current literature and provides some implications to the teacher preparatory programmes.